Proposals for the Multiparametric Design Application in Electrical Mechanical Engineering - Shevchenko V.V.; Minko A.N.; Stoychev V.T. (Problems of the Regional Energetics)
The aim of the work is to obtain practical results for the electrical machines multiparametric de-sign application, to conduct a comparative analysis of the parametric and multiparametric design results of a turbogenerator and its elements when the load changes; to confirm the prospects the multiparametric design application. Currently, it is possible to use mathematical models when designing, and use parametric synthesis to optimize one specific parameter, which in certain cas-es turns out to be sufficient. The peculiarity of electric machines calculation and design is the necessity of simultaneous checking of all interrelated parameters (mechanical, electromagnetic, thermal) with any changes. The structure design with simultaneous control of several variables cannot be performed using one stage of parametric design; additional calculations are necessary. In this case, multi-parameter design is necessary, but it requires longer preparation for design work and higher qualifications of personnel. Therefore, it is necessary to understand in which cases it is advisable to switch from parametric to multiparametric design. The work goal set is achieved by comparing the results of a turbogenerator, stator core and busbar designing using parametric and multiparametric design. The most important is to obtain the results of comparison of a complex electromechanical system parametric and multiparametric design (turbogenerator, its individual unit and element), including when the parameters of various physical processes change, performing a comparison of the obtained results, confirming the feasibility of carrying out multiparametric design. The significance of the obtained results is that practical examples of the multiparameter modeling use are shown. Using multiparametric design, not only a busbar refined form with increased repair and operational reliability was obtained, but the proposed so-lution economic advantages were also indicated.